Vascular Stress Signaling in Hypertension. Issue 7 (2nd April 2021) - Cicalese, Stephanie M.; da Silva, Josiane Fernandes; Priviero, Fernanda; Webb, R. Clinton; Eguchi, Satoru; Tostes, Rita C.
Abstract : Cells respond to stress by activating a variety of defense signaling pathways, including cell survival and cell death pathways. Although cell survival signaling helps the cell to recover from acute insults, cell death or senescence pathways induced by chronic insults can lead to unresolved pathologies. Arterial hypertension results from chronic physiological maladaptation against various stressors represented by abnormal circulating or local neurohormonal factors, mechanical stress, intracellular accumulation of toxic molecules, and dysfunctional organelles. Hypertension and aging share common mechanisms that mediate or prolong chronic cell stress, such as endoplasmic reticulum stress and accumulation of protein aggregates, oxidative stress, metabolic mitochondrial stress, DNA damage, stress-induced senescence, and proinflammatory processes. This review discusses common adaptive signaling mechanisms against these stresses including unfolded protein responses, antioxidant response element signaling, autophagy, mitophagy, and mitochondrial fission/fusion, STING (signaling effector stimulator of interferon genes)-mediated responses, and activation of pattern recognition receptors. The main molecular mechanisms by which the vasculature copes with hypertensive and aging stressors are presented and recent advancements in stress-adaptive signaling mechanisms as well as potential therapeutic targets are discussed.